The design and conduct of Project RedDE: A cluster-randomized trial to reduce diagnostic errors in pediatric primary care. (April 2019) - Bundy, David G; Singh, Hardeep; Stein, Ruth EK; Brady, Tammy M; Lehmann, Christoph U; Heo, Moonseong; O'Donnell, Heather C; Rice-Conboy, Elizabeth; Rinke, Michael L
Background: Diagnostic errors contribute to the large burden of healthcare-associated harm experienced by children. Primary care settings involve high diagnostic uncertainty and limited time and information, creating ideal conditions for diagnostic errors. We report on the design and conduct of Project RedDE, a stepped-wedge, cluster-randomized controlled trial of a virtual quality improvement collaborative aimed at reducing diagnostic errors in pediatric primary care. Methods: Project RedDE cluster-randomized pediatric primary care practices into one of three groups. Each group participated in a quality improvement collaborative targeting the same three diagnostic errors (missed diagnoses of elevated blood pressure and adolescent depression and delayed diagnoses of abnormal laboratory studies), but in a different sequence. During the quality improvement collaborative, practices worked both independently and collaboratively, leveraging general quality improvement strategies (e.g. process mapping) in addition to error-specific content (e.g. pocket guides for blood pressure norms) delivered during the intervention phase for each error. The quality improvement collaborative intervention included interactive learning sessions and webinars, quality improvement coaching at the team level, and repeated evaluation of failures via root cause analyses. Pragmatic data were collected monthly, submitted to a centralized data aggregator, and returned to the practices in the form of run charts comparing each practice's progress over time to that of the group. The primary analysis used patients as the unit of analysis and compared diagnostic error proportions between the intervention and baseline periods, while secondary analyses evaluated the sustainability of observed reductions in diagnostic errors after the intervention period ended. Results: A total of 43 practices were recruited and randomized into Project RedDE. Eleven practices withdrew before submitting any data, and one practice merged with another participating practice, leaving 31 practices that began work on Project RedDE. All but one of the diverse, national pediatric primary care practices that participated ultimately submitted complete data. Quality improvement collaborative participation was robust, with an average of 63% of practices present on quality improvement collaborative webinars and 85% of practices present for quality improvement collaborative learning sessions. Complete data included 30 months of outcome data for the first diagnostic error worked on, 24 months of outcome data for the second, and 16 months of data for the third. Lessons learned and limitations: Contamination across study groups was a recurring concern; concerted efforts were made to mitigate this risk. Electronic health records played a large role in teams' success. Conclusion: Project RedDE, a virtual quality improvement collaborative aimed at reducing diagnostic errors in pediatric primary care, successfully recruited and retained a diverse, national group of pediatric primary care practices. The stepped-wedge, cluster-randomized controlled trial design allowed for enhanced scientific efficiency.